Drama structures : a practical handbook for teachers - O'Neill, Cecily; Lambert, Alan. (London : Hutchinson, 1984)
A teacher's manual providing lesson structures for drama and learning activities. With notes on practical teaching problems and possible developments for each sequel
Includes bibliography references and index.
Keywords: Drama